Effect of Vacancy Defects on the Electronic Structure and Optical Properties of GaN - Lili Cai; Cuiju Feng (Journal of Nanotechnology)
The effect of gallium vacancy (VGa) and nitrogen vacancy (VN) defects on the electronic structure and optical properties of GaN using the generalized gradient approximation method within the density functional theory were investigated. The results show that the band gap increases in GaN with vacancy defects. Crystal parameters decrease in GaN with nitrogen vacancy (GaN:VN) and increase in GaN with gallium vacancy (GaN:VGa). The Ga vacancy introduces defect levels at the top of the valence band, and the defect levels are contributed by N2p electron states. In addition, the energy band shifts to lower energy in GaN:VN and moves to higher energy in GaN:VGa. The level splitting is observed in the N2p states of GaN:VN and Ga3d states of GaN:VGa. New peaks appear in lower energy region of imaginary dielectric function in GaN:VN and GaN:VGa. The main peak moves to higher energy slightly and the intensity decreases.